Mechanical analysis of full-scale accelerated pavement loading facility based on multi-body dynamics. Issue 1 (1st January 2018) - Guan, Zhiguang; Feng, Jinxiang; Wu, Qian; Zhang, Peng
ABSTRACT: It is intended that the pavements need to be designed to accomplish better performance due to the continuous increases of traffic volumes, vehicle loads and tyre pressure, especially for the channelized traffic. To achieve this objective, the method of accelerated pavement testing is used to directly optimize the asphalt pavement design. Therefore, the quality of the accelerated pavement testing facility plays an important role in optimizing the pavement design. In order to improve the success rate of the facility, the mechanical analysis of the accelerated pavement loading facility based on multi-rigid-body dynamics is carried out before the design and fabrication, so as to establish the virtual prototype of loading carriage; the multi-body dynamic equations are obtained according to the Newton–Euler formula; the force and displacement of each joint are simulated by using the MSC ADAMS software, and the results of stimulation meet the requirement; a full-scale accelerated loading testing (ALT) system with independent intellectual property right is developed. The ALT can be operated in single-axle or dual-axle loading mode, which is better than the existing facilities. The experiment indicates that the quality of the ALT, which is analysed based on multi-body dynamic, is excellent.